19 Anxiolysis for laceration repair in children: A survey of pediatric emergency providers in Canada. (29th October 2021) - Kumar, Kriti; Ali, Samina; Sabhaney, Vikram; Trottier, Evelyne D; Drendel, Amy; Shah, Amit; Bhatt, Maala; Poonai, Naveen
Abstract: Primary Subject area: Emergency Medicine - Paediatric Background: Laceration repair accounts for half of procedures performed in pediatric emergency departments. Although commonly used, topical anesthetics do little to alleviate emotional distress, particularly in young children. Intranasal midazolam is frequently used but is not consistently effective. Intranasal dexmedetomidine (IND) is a new and potentially effective anxiolytic but clinical uptake is limited by a lack of pediatric data. Objectives: Our objective was to understand pediatric emergency providers' willingness, preferences, and perceived barriers surrounding anxiolysis for laceration repair in children, to inform the design of a future clinical trial of IND. Design/Methods: This was an online survey of Canadian pediatric emergency providers listed in the Pediatric Emergency Research Canada database. The survey was developed according to published guidelines and featured a vignette of a 3-year-old distressed child requiring laceration repair. It was hosted on the Research Electronic Data Capture platform in English and French, and was disseminated from September to December 2020. The primary outcome was the proportion of respondents that would provide anxiolysis. Secondary outcomes included perceived barriers to IND use. Data were reported using summary statistics. Results: The response rate was 155/225 (68.9%), of which 98/141 (70%) were Royal College accredited pediatric emergency physicians. For 129/147 (88%) of respondents, 80-100% of their patients were children. 123/146 (84%) had > 6 years independent practice experience and 126/146 (86%) performed > 4 laceration repairs per month. 127/148 (86%) believed that > 25% of children experienced distress significant enough to require physical restraint during laceration repair. 116/148 (78%) indicated they would provide anxiolysis, mainly as intranasal benzodiazepines, such as midazolam (100/109, 92%). 95/148 (64%) indicated that they would consider IND if evidence suggested it was effective. Common perceived barriers included inadequate personal (114/145, 79%) and nursing (109/145, 75%) experience with IND, and lack of formulary access to IND (60/145, 41%). Conclusion: Most pediatric emergency providers believe that laceration repair in a young child is distressing and would provide anxiolysis. Most providers would consider IND if there was evidence of benefit, suggesting that favourable findings from a clinical trial would have good clinical uptake.